Applications of inspection games (Mathematical Modelling and Analysis, 2004)
An inspection game is a mathematical model of a non‐cooperative situation where an inspector verifies that another party, called inspectee, adheres to legal rules. The inspector wishes to deter illegal activity on the part of the inspectee and, should illegal activity nevertheless take place, detect it with the highest possible probability and as soon as possible. The inspectee may have some incentive to violate his commitments and violation, if observed, will incur punishment. Therefore if he chooses illegal behaviour, the inspectee will wish to avoid detection with the highest possible probability. Three examples of applications are presented. The first one deals with random controls in public transportation systems. The second one describes the problem of verification of arms control and disarmament in a very general way. The third one deals with inspections over time which are important in the context of non‐proliferation verification.Kontrolės lošimų taikymaiSantrauka. Kontrolės lošimas yra matematinis modelis tam tikrų nekooperacinių situacijų, kai inspektorius kontroliuoja kitą pusę, skatindamas korektišką elgesį. Inspektorius turi atbaidyti uždraustus veiksmus su kuo galima didesne tikimybe ir kuo greičiau. Tai reiškia, kad už nustatytų taisyklių pažeidimą mokama tam tikra bauda ir šie pažeidimai aptinkami su maksimalia tikimybe. Straipsnyje nagrinėjami trys šio modelio taikymo pavyzdžiai: atsitiktinė visuomeninio transporto keleivių kontrolė, ginklų kontrolės modelis ir paplitimo ribojimo per tam tikrą laiką modelis.First Published Online: 14 Oct 2010